Are public sector power supply organizations public-centered in developing countries? Servqual investigation / Warda Shahid Hamid ... [et. al] - Shahid Hamid, Warda; Ayyaz, Mubashir; Raza, Adnan; Kashif, Muhammad; Langrial, Sitwat (2011)
The study aims to investigate perceived service quality of Pakistan‟s only public sector power services provider. Primary data is collected from 300 randomly selected power supply consumers who visited different local places, during a two-month data collection period. The respondents were asked to fill in a questionnaire carrying 22 items based on SERVQUAL dimensions; reliability, tangibility, assurance, responsiveness, and empathy. There are major deficiencies noted in the service provision of GEPCO however, the SERVQUAL proved to be reliable when applied to measure the service quality of public sector organization. The scope of this research is limited to a single unit of power supply services which can be justified by considering the uniqueness of idea to investigate the service quality of power supply service as it has been initiated for the first time in Pakistani context. The study contributes theoretically towards successful application of SERVQUAL to public sector organizations operating in a developing country and will also help the local authorities in improving the service quality of country‟s major power supply company.